IMPLEMENTASI KEBIJAKAN ALOKASI DANA DESA DI WILAYAH KECAMATAN AIRMADDIDI KABUPATEN MINAHASA UTARA - Marjuanti, Eka (Universitas 17 Agustus 1945 Surabaya, 2015)
The purpose of this study is to provide an overview of the implementation of the VillageFund Allocation in District Airmadidi North Minahasa Regency, as well as contributingfactors and obstacles affecting the implementation and the strategy that should be donewithin the framework of the successful implementation of the policy but it also willprovide recommendations to the local government in the management of AllocationVillage fund. The method used in this research is qualitative descriptive method, wherethe main instrument in the study is the researchers themselves. Sources of data used isthe source of primary data and secondary data relating to the circumstances of empiricalimplementation of the Policy. The results showed that the implementation of the policyof the Village Fund Allocation (ADD) in the district of Minahasa UtaraberjalanAirmadidi quite smoothly. However, if it is linked to the achievement of objectives, theimplementation of the Village Fund Allocation (ADD) in the District of North MinahasaRegency Airmadidi not optimal. Some of the factors that affect the implementation ofthe Village Fund Allocation (ADD) in District Airmadidi North Minahasa Regency iscommunication, resource capabilities, attitudes executor, bureaucratic structure, and thesize and environmental policy objectives. Keywords: Policy Implementation, VillageFund Allocation, Airmaddidi, North Minahasa regency